2015 European Conference on Optical Communication (ECOC) 2015
DOI: 10.1109/ecoc.2015.7341912
|View full text |Cite
|
Sign up to set email alerts
|

Waveguide integrated InP-based photodetector for 100Gbaud applications operating at wavelengths of 1310nm and 1550nm

Abstract: We demonstrate a waveguide integrated pin-photodetector chip for 100Gbaud applications operating from the O-band to the L-band. By means of the photodetector chip 3rd order interception point measurements at highest reported frequencies up to 130GHz are presented

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In 2013, a packaged WGPD integrated with a verticallytapered spotsize converter and a 1 × 4 MMI coupler was fabricated [39] ; this device was composed of an array of 4 PDs in order to increase the saturation current and it had 30 GHz 3 dB bandwidth and high output power of 7.5 dBm at 20 GHz. In the same year, a PD with above 90 GHz 3 dB bandwidth was demonstrated [40] . In Ref.…”
Section: Research Hotspots Of Photodetectorsmentioning
confidence: 97%
“…In 2013, a packaged WGPD integrated with a verticallytapered spotsize converter and a 1 × 4 MMI coupler was fabricated [39] ; this device was composed of an array of 4 PDs in order to increase the saturation current and it had 30 GHz 3 dB bandwidth and high output power of 7.5 dBm at 20 GHz. In the same year, a PD with above 90 GHz 3 dB bandwidth was demonstrated [40] . In Ref.…”
Section: Research Hotspots Of Photodetectorsmentioning
confidence: 97%
“…The capacity of network systems that require state-of-the-art pin photodiodes (pin-PDs) is now approaching 800 Gbit/s, which uses a baud rate of 100 Gbaud. Studies on such high-speed pin-PDs for 100-Gbaud operation were conducted but used a waveguide structure [17,18]. Our approach is developing such high-speed pin-PDs with a vertical illumination structure [19].…”
Section: Inverted P-down Pin Photodiodes (Pin-pds)mentioning
confidence: 99%
“…2. For example, Zhou et al [16] proposed a waveguideintegrated PIN-PD based on the research of Runge et al [22] and obtained a linear photocurrent of 17 mA with an RF output power of +4.6 dBm at 20 GHz. Itakura et al [13] demonstrated a backside-illuminated PIN-PD using AlN flip-chip bonding with a 70 μm junction diameter and 0.8 μm thick intrinsic layer.…”
Section: Introductionmentioning
confidence: 99%